2020
DOI: 10.1177/0273475320946828
|View full text |Cite
|
Sign up to set email alerts
|

Selling-to-Teach: A Didactical Look at the Natural Integration Between Teaching and Selling

Abstract: This article examines whether educators’ use of selling activities (selling-to-teach) based on the seminal sales process can improve perceived and actual learning. By viewing the teaching interaction as a sales situation, the authors suggest professors can help students realize their need for learning just as a salesperson helps a prospect realize a need for a product or service. Leveraging the theoretical communication commonalities in teaching and selling, we posit that selling-to-teach will positively affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 101 publications
(178 reference statements)
0
2
0
Order By: Relevance
“…Educational technology companies offer free trials and subscriptions to propose solutions for pandemic pedagogy (Williamson et al, 2020), but technology alone may not be the answer. Crittenden et al (2010) aver that technology can usurp control; for example, the control that a salesperson has at a sales call or relatedly the teacher’s control in the classroom (Rippé et al, 2020). It would be remiss to think technology is the only solution for fixing all online teaching issues, especially because many educators are averse to teaching online and question the legitimacy of online education (Crittenden, 2020; Eastman & Swift, 2001).…”
mentioning
confidence: 99%
“…Educational technology companies offer free trials and subscriptions to propose solutions for pandemic pedagogy (Williamson et al, 2020), but technology alone may not be the answer. Crittenden et al (2010) aver that technology can usurp control; for example, the control that a salesperson has at a sales call or relatedly the teacher’s control in the classroom (Rippé et al, 2020). It would be remiss to think technology is the only solution for fixing all online teaching issues, especially because many educators are averse to teaching online and question the legitimacy of online education (Crittenden, 2020; Eastman & Swift, 2001).…”
mentioning
confidence: 99%
“…Social media enables social listening, which TVET colleges can use to create marketing and recruitment tools, offer career opportunities, encourage collaboration and teach (Benson & Morgan 2018). Literature suggests that social media marketing research in the higher education sector has focused on a few select issues, such as student recruitment (Le, Dobele & Robinson 2019;Lu & Miller 2019;Rippé et al 2018), consolidating student loyalty (Garza & Royo 2019) and brand recognition (Smedescu 2014). However, Bonilla Quijad et al (2022) state that social media can build quality relationships with users by creating brand communities for advertisement purposes, generating electronic word-of-mouth marketing and managing relationships with key stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Experiential learning was found to be important to both sales managers and sales representatives when hiring entry-level employees. Rippé et al (2020) posited that key selling techniques could be applied to teaching and found a correlation between some sales processes and improved student learning. Mantel et al (2002) described a program redesign that included three separate classes and integrated a feedback loop as well as self-assessment, key parts of Kolb's (1984) experiential learning theory.…”
Section: Curriculum Designmentioning
confidence: 99%